DETECTION OF A RARE OLIGO(A) REPEAT TRACT MUTATION (8As→7As) IN THE SEQUENCE ENCODING THE LA/SS-B AUTOANTIGEN - Semsei, Imre (2007)
Several diseases are characterized by the presence of point mutations, which are amenable to molecular detection using a number of methods including PCR. However, certain mutations are particularly difficult to detect due to factors such as low abundance or the presence of special (e.g. oligo-nucleotide repeat) sequences. The mutation 7A in the oligoA sequence of the exon 7 of the gene encoding La autoantigen is difficult to detect at the DNA and even RNA level due to both its estimated low abundance and its differentiation from the wild type 8A sequence. This paper describes a technique in which amplification of the excess wild type 8A La sequence is suppressed by a peptide nucleic acid (PNA) during a nested PCR step. Detection of the amplified 7A mutant form was then performed by simple electrophoresis following a final primer extension step with an infrared dye-labeled primer. This technique allowed us to detect the mutation in 3 of 7 individuals harboring serum IgG antibodies reactive with a B cell neo-epitope in the 7A-mutant protein product. We propose that this method is a viable screening test for mutations in regions containing simple poly-nucleotide repeats.